PERENCANAAN DINDING PENAHAN TANAH DI PERUMAHAN MUTIARA PALAS PERMAI KELURAHAN RUMBAI BUKIT KECAMATAN RUMBAI KOTA PEKANBARU - Fitridawati Soehardi; Juliper Marpaung; Virgo Trisep Haris (Prodi Magister Teknik Sipil Unsyiah, 2021)
The cliff in the Mutiara Palas Indah housing estate, Rumbai Bukit sub-district, Rumbai sub-district, Pekanbaru City, which experienced a landslide at the end of 2019, was caused by quite heavy rain. So it is necessary to plan soil reinforcement using cantilever type retaining walls using reinforced concrete to avoid landslides, with the results of the analysis of the landslide area using the simplified bishop method, the safety factor on this cliff has (F = 1,388 ) after getting the factor value If it is safe, it is planned that the dimensions of the cantilever type retaining wall have a height (H) = 6 meters, a wall thickness (H1) = 0,6 meters, a soil height in front of the wall (H2) = 0,7 meters, a wall height from ground level H3) = 4,7 meters, width (B) = 3,6 meters, the width of the front wall tread (B1) = 1,2 meters, the thickness of the lower wall (B2) = 0,6 meters, and the wall thickness (B3) = 0,4 meters. Then the results obtained are stability against overturning Fgl =3,604 1,5 (okay), stability against shear Fgs =2,279 1,5 (okay), and stability against bearing capacity collapse F = 18,218 3 (okay).